25. SOME FACTORS RELATED TO SLEEP DISORDERS IN HEAD AND NECK CANCER PATIENTS AT K HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: To describe some factors related to sleep disorders in patients with head and neck cancer at National Cancer Hospital in 2023.Materials and methods: A cross-sectional descriptive study was conducted on 200 patients with head and neck cancer who were undergoing radiation therapy at the Head and Neck Radiation Department, K Hospital, from April to August 2023. The Pittsburgh Sleep Quality Index (PSQI) was used for evaluation.Results: Patients with poor sleep accounted for up to 3/4 of the participants in the study (75%). The factors related to the quality of sleep in patients with head and neck cancer, when analyzed using univariate logistic regression, included income, the method of radiation or concurrent chemoradiation treatment, and pain episodes.Conclusion: Poor sleep quality is very common in head and neck cancer patients (75%), and sleep disorders are associated with economic status, pain episodes, as well as radiation and chemotherapy treatments.
Keywords: sleep disorders; head and neck cancer; radiation therapy